Karate: Alat yang efektif untuk meningkatkan fungsi sosial, emosional, dan eksekutif siswa dengan autisme - Kurniawan, Rama; Yusti Sianti, Ega; Annisaa, Annisaa; Rohana, Suni (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Patients with Autism Spectrum Disorder (ASD) are increasing daily, requiring appropriate intervention. Martial arts can improve their social, emotional, and executive functioning. This study uses karate martial art to reduce social dysfunction, emotional dysfunction, and stereotyped behavior in children with autism. The Single Subject Research (SSR) method was used with an A-B design that includes two research stages: baseline and intervention stages. Data was collected using a questionnaire adapted from ICD-10 and DSM-IV once a week. The samples used were four children with autism in SLB Lab UM. After training for six weeks, the data were analyzed using the SSR method to present the results in graphical form. The study results illustrated that the emotional, social, and executive functions in children with ASD increased. Karate training can be used as therapy for children with autism to improve and develop their social, emotional, and executive functions. This research has a limited number of involved subjects and needs an extended duration of intervention for future research. This research confirmed that karate could be an alternative therapy to improve the development of students with autism.